Estrategias pedagógicas y su incidencia en la discalculia de los estudiantes de básica elemental de la unidad educativa Juan Montalvo período 2021 – 2022 - Vergara Vera, Alicia Maria (2022)
Dyscalculia in the teaching-learning of mathematics of the elementary school students of the Juan Montalvo Educational Unit, the objective proposed in this study was to analyze the incidence and the effects considered as essential in terms of the achievement of skills of the pedagogical strategies applied. by teachers, in the different mathematical processes with a more competent, analytical progress that students develop in daily activities, without having greater learning difficulties. This development project was carried out in the Juan Montalvo Educational Unit of the Buena Fe canton, as well as providing solutions to the problems presented in the difficulties detected in learning mathematics, as a study problem they have as background the teaching-learning processes in the pedagogical strategies, carried out by teachers at the beginning of the school year, taking into account the diagnosis applied in the research, in which situations suffered by students as a result of cognitive, social or educational deficiencies were identified